Non-systematic Review of Financial Sustainability and Financial Distress - Raza, Hamad; Gillani, Syed Muhammad Ahmad Hassan; Ramakrishnan, Suresh; Ramakrishnan, Suresh; Gillani, Syed Muhammad Afraz Hassan; Qureshi, Muhammad Imran (International Journal of Psychosocial Rehabilitation, 2020)
Every business entity starts its operations for the purpose of earning profit for undefine time period. Beside earning profit, firms also emphasize on their growth and business expansion. However, due to poor financial planning or unseen factors, firms could not achieve targets and eventually face financial distress and bankruptcy. Once any business fails or bankrupt then it damages not only business its self but also damages many stakeholders like banks, suppliers, creditor and economy over all. In past, particularly in recent financial crisis many researchers and practitioners are engaged in developing the models which can predict financial failure. This study conducted a nonsystematic review on the development different models related to financial distress and observed that which models used which technique and what factors (variables) have been incorporated. Moreover, this study highlighted main features and also criticized drawback of each model. As discussed earlier that every company wants to grow, but this growth must be rational and sustainable. If growth is not sustainable then it may lead towards financial trouble. Therefore, this study suggests that if sustainable growth rate (SGR) will be incorporated in prediction modeling than accuracy of models can be improved.